Contexto de influência no processo de criação de políticas públicas educacionais do campo no governo de Luis Inácio Lula da Silva (2005-2010) - Marques, Leandro Mesquita (2021)
The present study analyzes how countryside Education’s discussions can be expanded. More specifically, this work aims to understand how public policies for Country Education in the PT government of Luís Inácio Lula da Silva between 2006 and 2010 emerged as well as the context of influence(s), that is: which social actors (Social Movements, intellectuals, political agents…), most contributed in the construction process underlying the creation of these policies. The document that we analyze is the “Educação do Campo: Marcos normativos” of 2012 produced by the Secretariat of Continuing Education, Literacy, Diversity and Inclusion – SECADI. Therefore, the work is divided into four chapters. The first chapter lists the central categories in which this work is based, as well as, the authors and works discussed in the process of weaving this dissertation. The recurrent discussion in the second chapter, concerns the history and principles of Rural Education and the Public Policy for Rural Education in Brazil. Described in the third chapter are the regulations included in the analyzed document – mentioned above – and their main characteristics and axioms. The fourth chapter establishes connections on how Social Movements, Universities and Agents of Neoliberalism influenced the creation of public policies for Education in general and for the Countryside in particular. It concludes that, during the period of Lula's PT government; Neoliberalism conditioned the paths that educational policies in Brazil took. However, with regard to public policies for Rural Education, there was a tangible and sensitive role of the Social Movements as protagonists in the creation of various policies, including the expansion of resources allocated to the National Program for Education in Agrarian Reform (PRONERA). It emphasizes, in the four chapters in which this dissertation is divided, that the public policy of Education in the Countryside is the result of the incessant struggle of Social Movements active in the Countryside and that this, in turn, runs in the wake of the struggle for Agrarian Reform.